Relationship between obesity and antipsychotic drug use in the adult population: A longitudinal, retrospective claim database study in Primary Care settings - Antoni Sicras-Mainar (Dove Medical Press, 2008)
Antoni Sicras-Mainar1, Ruth Navarro-Artieda2, Javier Rejas-Gutiérrez3, Milagrosa Blanca-Tamayo41Planning Management, Badalona Serveis Assistencials S.A., Badalona, Barcelona, Spain; 2Medical Documentation Service, Hospital Germans Trías i Pujol, Badalona, Barcelona, Spain; 3Health Outcomes Research Derpartment, Medical Unit, Pfizer Spain, Alcobendas, Madrid, Spain; 4Department of Psychiatry, Badalona Serveis Assistencials S.A., Badalona, Barcelona, SpainObjective: To describe the association between obesity and the use of antipsychotic drugs (APDs) in adult outpatients followed-up on in five Primary Care settings.Methods: A longitudinal, retrospective design study carried out between July 2004 and June 2005, in patients who were included in a claim database and for whom an APD treatment had been registered. A body mass index (BMI) <30 kg/m2 was defined as obesity. The main measurements were: use of APDs, demographics, medical background and co-morbidities, and clinical parameters. Logistic regression analysis and ANCOVA with Bonferroni adjustment were applied to correct the model.Results: A total of 42,437 subjects (mean age: 50.8 (18.4) years; women: 54.5%; obesity: 27.3% [95% confidence intervals (CI), 26.9%–27.7%]) were analyzed. A total of 1.3% of the patients were receiving APDs, without statistical differences in distribution by type of drug (typical: 48.8%; atypical: 51.2%). Obesity was associated with the use of APDs [OR = 1.5 (CI: 1.3–1.8)], hypertension [OR = 2.4 (CI: 2.2–2.5)], diabetes [OR = 1.4 (CI: 1.3–1.5)] and dyslipidemia [OR = 1.3 (CI: 1.2–1.4)], p < 0.0001 in all cases. BMI was significantly higher in subjects on APDs; 28.8 vs. 27.3 kg/m2, p = 0.002, and remained higher after adjusting by age and sex (mean difference 0.4 (CI: 0.1–0.7), p < 0.01). After adjusting by age, sex and the Charlson index, obese subjects generated higher average annual total costs than nonobese subjects; 811 (CI: 787–835) vs. 694 (CI: 679–709), respectively, p < 0.001.Conclusions: Obesity was associated with the use of APDs, regardless of the type of drug, and with the presence of hypertension, diabetes and dyslipidemia. Obesity was also associated with substantially higher health care costs.Keywords: Obesity, claim database, retrospective study, antipsychotic use, Primary Care setting, resources utilization, health care costs